Evaluation of the Implementation of the Ideal Online Learning System in Frontier, Outermost, and Disadvantaged Regions (3T) - Erwin Randjawali; Erfy Melany Lalupanda; Riwa Rambu Hada Enda; Vidriana Oktoviana Bano; Mayun Erawati Nggaba; Yulita Milla Pakereng; Alexander Kaka; Victor Soleman Lawa Lulu (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to evaluate the implementation of an ideal online learning system that has been designed using the ADDIE model in the 3T (Front, Outermost, & Disadvantaged) area in East Sumba Regency. This research method uses descriptive qualitative. This research was conducted at SDI Waingapu 2 and SMP Negeri 1 Waingapu. The subjects of this study were teachers, students, parents, and principals of SDI Waingapu 2 and SMP Negeri 1 Waingapu, as well as the East Sumba Regency Office. Data collection techniques in this study used interviews, questionnaires, observation, and document studies. The data analysis technique is qualitative data analysis which includes data reduction, data presentation, and drawing conclusions. The results show that the Ideal Online Learning System for East Sumba Regency has been implemented by SDI Waingapu 2 and SMP Negeri 1 Waingapu following the Guidelines for the Ideal Distance Learning System in East Sumba Regency by the Education Office, both by students, teachers, parents, school principals, as well as the East Sumba District Education Office. However, obstacles still hinder the implementation of online learning, such as unstable internet connections and teacher skills in utilizing learning technology. The ideal online learning system that has been developed is then used as consideration for policymakers to improve the quality of education in East Sumba Regency as one of the Disadvantaged, Frontier, and Outermost regions.